Exploring Irish high-performance sports coaches' understanding and application of reflective practice. Issue 2 (4th March 2023) - Lowry, Simon; Swanson, Steve; Kelly, Seamus
ABSTRACT: The role and efficacy of reflective practice in sport continues to be critiqued, despite the increasing research evidence in its support. This study explored the understanding of Irish high-performance sport coaches in terms of a) purposes, b) processes, c) enablers and barriers, and d) knowledge sources of reflective practice. Semi-structured interview data were acquired from Irish male rugby union (n = 5) and hockey (n = 4) coaches for analysis. The participants' reflective practice-based descriptions revealed findings related to the four inquiry criteria. First, reflective practice incorporated purposes such as problem solving and contribution towards various aspects of learning and development for the coach and their athletes. Second, reflective practice processes were cyclical and included questioning, self-questioning, and feedback. Third, the nature of high-performance sport involved several enablers (mentors and video-based technology) and barriers (time, results, and tactical and player demands). Fourth, the knowledge sources (i.e. pedagogical approaches) towards reflective practice may have limited certain participants' ability to become critically reflective practitioners. The findings have educational implications for preparing coaches to deal with the challenges related to working in a highly demanding, results-dependent, and high-pressure sport environment.